New labour market developments in the context of digitalisation and social change: Report of Abstracts - Latvijas Universitāte. 80. starptautiskā zinātniskā konference (Latvijas Universitāte, 2022)
The conference session aims to provide a platform/opportunity for scholars, researchers and professionals from different disciplinary backgrounds to meet, exchange ideas, findings, research results and discuss the topical issues related to the labour market developments in the context of digitalisation and social change. The session is supported by the project The Economic Integration of the Nordic‐Baltic Region through Labour, Innovation, Investments and Trade – LIFT
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics; Public Services; Economic development; Employees